DETERMINANTS ON AUDIT QUALITY OF CITY INSPECTORATES IN SOUTH SULAWESI PROVINCE - Usman A.; Nagu N.; Syahrir; Sundari S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2017)
This study aims to identify and analyze the effect of leadership style on self-efficacy, the effect of leadership style on emotional exhaustion; self-efficacy influences the emotional exhaustion, and emotional exhaustion on audit quality. This study uses a quantitative approach. The population in this study was all auditors in city inspectorates in South Sulawesi Province, Indonesia. The sampling technique used in this research is purposive sampling where the sampling is based on the consideration or criteria in accordance with the purpose of research. These research data will be obtained by filling out a questionnaires, and direct interviews with respondents. Data are collected through questionnaires and interviews, and are analyzed using quantitative and descriptive analysis techniques.